Multiwavelength ytterbium-Brillouin random Rayleigh feedback fiber laser. (9th February 2018) - Wu, Han; Wang, Zinan; Fan, Mengqiu; Li, Jiaqi; Meng, Qingyang; Xu, Dangpeng; Rao, Yunjiang
Abstract: In this letter, we experimentally demonstrate the multiwavelength ytterbium-Brillouin random fiber laser for the first time, in the half-open cavity formed by a fiber loop mirror and randomly distributed Rayleigh mirrors. With a cladding-pumped ytterbium-doped fiber and a long TrueWave fiber, the narrow linewidth Brillouin pump can generate multiple Brillouin Stokes lines with hybrid ytterbium-Brillouin gain. Up to six stable channels with a spacing of about 0.06 nm are obtained. This work extends the operation wavelength of the multiwavelength Brillouin random fiber laser to the 1 µ m band, and has potential in various applications.